ECONOMIC AND POLITICAL DIMENSIONS OF BILATERAL RELATIONS BETWEEN UZBEKISTAN AND GERMANY: CURRENT TRENDS AND FUTURE PROSPECTS - Farkhod Abdurakhmonov; Abdukodir Ismoilov Dilshod ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Since 2017, Uzbekistan’s foreign economic policy has undergone a significant transformation, marked by trade liberalisation, the strengthening of diplomatic relations, and the active attraction of foreign investment. As a result of these reforms, Uzbekistan has emerged as an increasingly active participant in the global economy. Notably, its cooperation with economically advanced partners, particularly the European Union and the Federal Republic of Germany, has witnessed substantial growth in trade, investment, and socio-economic collaboration. This article explores the evolving foreign economic relations between the Republic of Uzbekistan and the Federal Republic of Germany, focusing on the current level of trade and economic integration. It also assesses the prospects for further deepening bilateral cooperation. The analysis offers comprehensive insights into new joint initiatives and investment opportunities while evaluating the potential implications and long-term outcomes of these partnerships.